The effect of hay supplementation on performance of grazing alpaca in the Peruvian Andes - Enciso, M.; Gómez, C.; Osorio Zavala, Cesar Mauro (Kenya Agricultural and Livestock Research Organization, 2024)
Productivity of alpaca grazing rangelands in the Andes is often limited by the low availability and quality of those pastures during the dry season of the year. The use as supplements of forages cultivated during the rainy season in appropriate areas in the Andes may be a strategy to improve performance of alpacas. Therefore, the supplementation of oat-vetch pellets or oat hay was evaluated and compared with a control group without supplementation. Sixty-three female alpacas (15 months of age, 34 ± 1.0 kg BW), divided in three groups, grazing range pastures (6.1% crude protein and 61.3% NDF) during dry season in Puno region of the Peruvian Andes were used for the study. The supplement was offered daily after grazing (400 g/alpaca/day). The study lasted for 84 days with evaluations of weight gain and intake every 28 days. Weight gain was greater for animals supplemented with oat-vetch pellet (3.1 ± 0.27 kg) compared to oat hay (0.98 ± 0.33) (P≤ 0.05) while the control lost BW (0.64 ± 0.22). The total dry matter intake (pasture and supplement) was 502, 575.6 and 579.5 g / alpaca/ day for the control, oat-vetch pellet and oat hay group respectively indicating partial replacement of pasture by the supplement. Under the study conditions, the supplementation of oat-vetch pellets improved performance better than oats hay or no supplementation for alpacas grazing range pastures during the dry season.